Kepemimpinan Efektif dalam Meningkatkan Produktivitas Organisasi - Dian Pakaya; Niken Rahmawati; Muhamad Rifai Silama; Elyasari Lagarusu; Osorio Almeida (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Productivity is one of the main indicators of an organization’s success in achieving its goals. Amid dynamic environmental changes, effective leadership becomes a key factor that determines an organization’s ability to manage resources, motivate employees, and direct work processes. This article aims to examine the role of effective leadership in enhancing organizational productivity by reviewing the fundamental concepts of leadership, the characteristics of effective leaders, and the mechanisms through which leadership influences performance and productivity. The method used is a literature study by reviewing various sources related to leadership, human resource management, and organizational productivity. The results of the review indicate that effective leadership is reflected in the ability to build a vision, communicate clearly, empower employees, provide motivation, and apply leadership styles that are appropriate to the organizational context. Effective leadership contributes to increased productivity by creating a positive work climate, improving employee commitment, job satisfaction, and discipline. This article concludes that efforts to enhance organizational productivity cannot be separated from the development of leadership capacity at all managerial levels.